2021
DOI: 10.1101/2021.05.26.445820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Arginine-Rich Motif in the ORF2 Capsid Protein Regulates the Hepatitis E Virus Lifecycle and Interactions with the Host Cell

Abstract: Producing multifunctional proteins is one of the major strategies developed by viruses to condense their genetic information. Here, we investigated the molecular determinants of the multifunctionality of hepatitis E virus (HEV) ORF2 capsid protein. We previously identified 3 isoforms of ORF2 which are partitioned in different subcellular compartments to perform distinct functions. Notably, the infectious ORF2 (ORF2i) protein is the structural component of the virion, whereas the genome-free secreted and glycos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Indeed, by combining the gt3 p6 strain [15] and the highly transfectable PLC3 cells, we identified 3 forms of the ORF2 capsid protein that perform distinct functions in the HEV lifecycle and display different sequences, post-translational modifications and subcellular localization [6,14]. The ORF2i form is the component of infectious particles and derives from the assembly of intracellular ORF2i (ORF2intra) protein [8]. The ORF2i and ORF2intra proteins are not glycosylated and display the same sequence starting at Leu14 corresponding to the middle of the signal peptide (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, by combining the gt3 p6 strain [15] and the highly transfectable PLC3 cells, we identified 3 forms of the ORF2 capsid protein that perform distinct functions in the HEV lifecycle and display different sequences, post-translational modifications and subcellular localization [6,14]. The ORF2i form is the component of infectious particles and derives from the assembly of intracellular ORF2i (ORF2intra) protein [8]. The ORF2i and ORF2intra proteins are not glycosylated and display the same sequence starting at Leu14 corresponding to the middle of the signal peptide (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These glycosylated forms are produced by translocation of ORF2 proteins into the secretory pathway where they are N-glycosylated on two N-x-S/T sequons [14], O-glycosylated and sialylated, and quickly secreted [6,7]. They are cleaved by cellular proteases notably by the proprotein convertase furin [8]. Here, we capitalized on these distinctive features to generate and characterize four anti-ORF2 monoclonal antibodies, including three antibodies (P1H1, P2H1 and P2H2) directed against the ORF2i form and one antibody (P3H2) directed against the different ORF2 isoforms (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that the HEV capsid interacts with β-TRCP to block the ubiquitin-proteasome-mediated degradation of IκB which subsequently inhibits NF-κB activation (Surjit et al, 2012). Moreover, a recent preprint report suggested that the argininerich motifs of the N-terminal of ORF2 could serve as a nuclear location signal to direct the nuclear translocation of ORF2 therefore inhibit the downregulation of NF-κB-related signaling as well (Hervouet et al, 2021).…”
Section: Regulation Of Innate Immune Response and Cellular Signaling By Hepatitis E Virus-open Reading Framementioning
confidence: 99%